2021
DOI: 10.5194/nhess-21-1431-2021
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and risks of disaster data from social media: a systematic review of incident information

Abstract: Abstract. Compiling and disseminating information about incidents and disasters are key to disaster management and relief. But due to inherent limitations of the acquisition process, the required information is often incomplete or missing altogether. To fill these gaps, citizen observations spread through social media are widely considered to be a promising source of relevant information, and many studies propose new methods to tap this resource. Yet, the overarching question of whether and under which circums… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, the review identified the lack of combination of different methods as one of the key limitations of the research field. Stock (2018) provided another systematic review but focused on mining location information, whilst others have focused on more specific areas of the field (Wiegmann et al, 2021; Wilkins et al, 2021). Yan et al (2020) identified Twitter as a major source of VGI, and disaster and crisis management were among the topics highlighted as the most common application field.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the review identified the lack of combination of different methods as one of the key limitations of the research field. Stock (2018) provided another systematic review but focused on mining location information, whilst others have focused on more specific areas of the field (Wiegmann et al, 2021; Wilkins et al, 2021). Yan et al (2020) identified Twitter as a major source of VGI, and disaster and crisis management were among the topics highlighted as the most common application field.…”
Section: Related Workmentioning
confidence: 99%
“…A disaster is a dangerous event; it is not known exactly when it will occur, and it may be caused by nature or by humans [1]. Natural hazards, which cannot be predicted in advance, cause significant damage to human life, property, the environment, and agricultural products.…”
Section: Introductionmentioning
confidence: 99%
“…A disaster is a dangerous event; it is not known exactly when it will occur, and it may be caused by nature or by humans [1]. Disasters can pose a risk of economic loss in the form of the loss of livelihoods and/or damage to infrastructure.…”
Section: Introductionmentioning
confidence: 99%